Building Inspirational Islamic Education with the Flipped Learning Model and Canva to Solve 21st-Century Learning Problems - Elina Mazidatun Nikmah; Irma Soraya; Faten Skafi (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: Building Inspirational Islamic Education with the Flipped Learning Model and Canva to Solve 21st-Century Learning ProblemsObjective: This research study aims to create inspirational Islamic Education learning using the flipped learning model assisted by Canva to solve 21st-century learning problems. Methods: This research uses a qualitative research approach with a case study method. Data were collected using observation, interview, and documentation and were analyzed using the Miles and Huberman model. Results: The flipped learning model in Islamic education can increase students' enthusiasm for learning. Conclusion: One of the strategic steps teachers and schools can take to create inspiring Islamic religious education learning is using the flipped learning model assisted by Canva. Teachers and schools can create more inspiring and engaging Islamic Education (PAI) learning experiences by implementing the flipped learning model with the help of Canva as a supporting tool. Contribution: This research contributes to developing a flipped learning-based Islamic education that has not been widely applied in Indonesia.INDONESIAN: Membangun Pendidikan Agama Islam yang Inspiratif dengan Model Flipped Learning dan Canva sebagai Solusi Permasalahan Pembelajaran Abad 21Tujuan: Penelitian ini untuk menciptakan pembelajaran Pendidikan Agama Islam yang inspiratif dengan menggunakan model flipped learning berbantuan aplikasi canva sebagai Solusi Permasalahan Pembelajaran Pendidikan Agama Islam Abad 21. Metode: Penelitian ini menggunakan pendekatan penelitian kualitatif dengan metode studi kasus. Teknik pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Analisis data menggunakan model Miles dan Huberman. Hasil: Model pembelajaran flipped learning pada pelajaran Pendidikan Agama Islam dapat meningkatkan semangat belajar siswa. Kesimpuilan: Salah satu langkah strategis yang dapat dilakukan oleh guru dan sekolah untuk menciptakan pembelajaran pendidikan agama Islam yang inspiratif adalah dengan menggunakan model flipped learning berbantuan aplikasi Canva. Guru dan sekolah dapat menciptakan pengalaman belajar Pendidikan Agama Islam (PAI) yang lebih inspiratif dan menarik dengan menerapkan model pembelajaran flipped learning dengan bantuan Canva sebagai alat bantu. Kontribusi: Penelitian ini berkontribusi dalam mengembangkan model pembelajaran pendidikan agama Islam berbasis flipped learning yang belum banyak diterapkan di Indonesia.